(untitled) (International Journal of Physiotherapy, 2018)
Background: Football training reduces the flexibility of players. Lower flexibility in the knee and hip flexors may increase the risk of muscle strain injury. A method which increases the flexibility without a concomitant deficit in muscle performance will be meaningful for athletic performance and injury prevention for football players. The purpose of the current study was to investigate the acute effects of self-myofascial release via a foam roller on vertical jumps, speed, agility and flexibility of football players. Methods: It was a randomized, nonexperimental and comparative design. Participants were forty-two amateur football players (age: 24.3 ± 5.5 yr., height: 175.24± 4.3 cm, weight 69.03± 5.56 kg). They were divided randomly into four groups as control (CON), static stretching (SS), dynamic stretching (DS) and foam roller (FR). The CON performed five minutes jogging and seven and a half minute rest, the SS performed five minutes jogging and seven and a half minutes of static stretching, the DS performed five minutes jogging, and seven and a half minutes dynamic stretching, and the FRG performed five minutes jogging and seven and a half minutes foam roller intervention. Outcome measurements: After the stretching protocols, all groups performed vertical jumps (countermovement jump, squat jump, and horizontal jump), speed (10 and 30 m.), and agility (t-test) tests. One way ANOVA test was used for comparing results of the groups. Results: The FR and DS protocols were significantly better in speed, agility, and vertical jumps test when compared with the SS (P<0.01). Moreover, the FR and SS had significantly better flexibility than the DS and CON (P<0.01). Conclusion: According to the results of the present study, the acute effect of foam roller intervention is more appropriate for improving flexibility without a concomitant deficit in muscle performance than static and dynamic stretching protocols.